Factors affecting long acting and permanent contraceptive methods utilization among HIV positive married women attending care at ART clinics in Northwest Ethiopia - Abebaw Addis Gelagay; Digsu Negese Koye; Hedija Yenus Yeshita (BMC, 2018)
Abstract Background Globally, unintended pregnancy has been very high accounting for 27% of maternal deaths. Different studies noted that nearly half of HIV positive women who gave unintended birth were using contraceptive methods prior to their unintended pregnancy. This implies that contraceptive failure contributes to unintended pregnancy. Long-term and permanent contraceptive methods are safe and effective contraceptive options. In women who are using long acting and permanent methods, the unintended pregnancy rate is very low and it is almost the same both in typical and perfect users. However, there is limited information on factors that affect long acting and permanent contraceptive methods utilization among Human Immuno-deficiency Virus (HIV) positive women in Ethiopia. Therefore, the purpose of this study was to assess long acting and permanent contraceptive utilization and its associated factors. Methods An institution-based cross-sectional study was conducted among 505 married women attending care at Anti Retroviral Therapy (ART) clinics in Bahir Dar from March 16, 2014 to April 15, 2014. The data were collected using a structured and interviewer administered questionnaire. Both bivariate and multivariate logistic regressions were used to identify associated factors. Results A total of 505 married women participated in the study with a response rate of 99.6%. The utilization of long acting and permanent contraceptive methods (LAPMs) was 27.5% [95% CI, 23.8-31.5]. The multivariate analyses showed that women who were getting pre- anti retroviral therapy (Pre-ART) services [Adjusted Odds Ratio = 2.65, 95% confidence interval: 1.44, 4.86], had spousal discussion on family planning sometimes [Adjusted Odds Ratio = 6.03, 95% CI:2.42-15.01] and frequently [Adjusted Odds Ratio = 6.61, 95% confidence interval: 2.49-17.47], had previous experience on long acting contraceptive methods [Adjusted Odds Ratio = 9.06, 95% confidence interval: 5.38-15.26], no exposure to myths about LAPMs [Adjusted Odds Ratio = 2.07, 95% confidence interval: 1.24-3.45], had birth intention after 2 years [Adjusted Odds Ratio = 6.95, 95% confidence interval: 3.35-14.42], and no such intention [Adjusted Odds Ratio = 7.60, 95% confidence interval: 3.77-15.34] were factors significantly associated with utilization of long acting and permanent contraceptive methods. Conclusion The utilization of long acting and permanent contraceptive methods was relatively high. Discussion with partners on family planning, previous experiences of LAPMs, not hearing myths about LAPMs, women not started ART, and no birth intention were positively associated with LAPMs utilization. It is therefore recommended that health service providers need to make couples counseling on FP, undergo behavioral change communication (BCC) to avoid misconceptions/myths regarding LAPMs. Further research is also recommended to address the gaps mentioned in the limitation section and to explore the reason/s for not using LAPMs (qualitative study).